Identifikasi Tingkat Kerusakan dan Kinerja Fisik Jaringan Irigasi DI Cokro, Kabupaten Malang - Wiconarto Wiconarto; Yurnalisdel Yurnalisdel; Suhudi Suhudi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
A stable supply of irrigation water is a crucial factor for agricultural success, but its effectiveness depends heavily on the physical integrity of the irrigation network. This study aims to analyze the structural condition of physical assets and evaluate the performance of irrigation structures in the primary canal of the Cokro Irrigation District (DI), Jeru Village, Tumpang Subdistrict, Malang Regency. The evaluation focused on a 927-meter-long primary channel serving a 30-hectare rice field area. The research method used was quantitative descriptive, involving field surveys (inventory) and technical measurements in accordance with the standards set forth in Ministry of Public Works and Public Housing Regulation No. 12/PRT/M/2015. Primary data were obtained through visual inspections at 15 points along the primary channel and its ancillary structures to assess the extent of damage. Data analysis included calculating the percentage of network damage and determining the physical performance index. The results of the study indicate that the physical condition of the infrastructure is at the “cautionary maintenance” level. A total of 73.34% of the assets are in serviceable condition (Good and Slightly Damaged), but there are 26.67% of critical points categorized as Moderately Damaged, Severely Damaged, and Abandoned. The predominant forms of damage are sedimentation and the growth of wild vegetation that obstructs water flow. Based on calculations, the performance index of the Cokro irrigation system is 72.82%, which is classified as “Function impaired, requires repair.” The proposed technical recommendations are immediate rehabilitation at critical points and optimization of preventive maintenance to restore optimal water service functionality.